Legal Accountability and Ethical Considerations for Outcomes Driven by Artificial Intelligence in Business Operations - Matthias Holzhausen (Faculty of law Udayana University, 2024)
This paper critically examines the integration of Artificial Intelligence (AI) into business operations, focusing on the challenges of legal accountability and ethical considerations. It first traces the development of AI and its transformative impact on commerce, providing a basis for examining the key ethical and responsibility challenges. The paper presents research findings that highlight the complexity of assigning responsibility for AI-generated outcomes and discusses the different approaches in national and international legal frameworks for AI. It emphasizes the need for clear legal structures and ethical guidelines to govern the role of AI in business and society. The paper concludes by highlighting the importance of harmonized global frameworks to ensure the responsible integration of AI, addressing both theoretical and policy implications. The findings point to a significant shift in legal trends and societal impacts due to AI and emphasize the urgent need for ethical deployment to prevent the reinforcement of societal biases.